THE EXPOSURE EFFECTS OF PARAQUAT DICHLORIDE HERBICIDE ON HUMAN PULMONARY FIBROSIS - Widayana, I Gede Eka (Majority, 2014)
Abstract Paraquat(1,1−dimetil,4,4−bipiridilum) is one of active ingredients gramoxone type that most widely used in the world include Indonesia. Using of paraquat can damage many organs, one of organ is lung.The toxicity is characterized by the appearance of pulmonary edema, pulmonary alveolar membrane damage, and then develop into pulmonary fibrosis. The main pathogenesis of pulmonary fibrosis is through the formation of free radical with oxidative damage to lung tissue. Acute pulmonary edema and lung damage can occur in hours due to heavy exposure. Lung damage which develop into pulmonary fibrosis, appear on day 7 to 14 after consuming, is the most common cause of death The paraquat dichloride herbicides exposure can cause pulmonary fibrosis in humans. Toxic doses of paraquat dichloride which can lead to pulmonary fibrosis in human is 20 to 40 mg/kg weight. Key word: free radical, oxidative damage, paraquat diklorida, pulmonary fibrosis Abstrak Paraquat (1,1−dimetil,4,4−bipiridilum)merupakan salah satu bahan aktif herbisida jenis gramoxone yang paling banyak digunakan didunia termasuk di Indonesia. Penggunaan paraquat dengan sembarangan dapat merusak berbagai macam organ salah satunya adalah paru-paru. Toksisitas dikarakteristikan dengan munculnya edema pulmonum, kerusakan membran alveoli paru, dan kemudian berkembang menjadi fibrosis paru. Patogenesis utama terjadinya fibrosis paru adalah melalui terbentuknya radikal bebas denganoxidative damage kepada jaringan paru. Edem paru akut dan kerusakan paru bisa muncul dalam hitungan jam dikarenakan paparan yang berat, kerusakan paru kemudian berkembang menjadi fibrosis paru, yang merupakan penyebab tersering kematian, dan muncul biasanya pada hari ke 7 sampai hari ke 14 setelah mengkonsumsi. Paparan herbisida golongan paraquat diklorida menyebabkan suatu efek berupa fibrosis paru pada manusia. Dosis toksik paraquat diklorida yang dapat mengakibatkan fibrosis paru pada manusia adalah sebesar 20−40 mg/kgBB. Kata kunci: fibrosis paru, oxidative damage, paraquat diklorida, radikal bebas